2018
DOI: 10.1186/s40413-018-0220-5
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-specific IgE and IgG4 patterns among patients with different allergic diseases

Abstract: BackgroundIn addition to allergen-specific IgE (sIgE), allergen-specific IgG4 (sIgG4) antibodies are also involved in the immune response resulting from an allergen exposure. The aim of our study was to analyze sIgE and sIgG4 patterns in the most common allergic disorders: bronchial asthma, upper airway disorders and atopic dermatitis.MethodsIn this study a screening analysis of blood serum samples from 673 patients aged from 6 months to 17 years with different allergic entities was performed on microarrays. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Our results are completely in agreement with earlier epidemiological studies which reported higher IgE levels associated with bronchial responsiveness, a major component of the asthma phenotype, rhinitis and dermatitis [ 31 33 ]. In recent years, a high serum levels of IgE is used to predict the development of asthma, independent of other allergic factors.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are completely in agreement with earlier epidemiological studies which reported higher IgE levels associated with bronchial responsiveness, a major component of the asthma phenotype, rhinitis and dermatitis [ 31 33 ]. In recent years, a high serum levels of IgE is used to predict the development of asthma, independent of other allergic factors.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that serological IgG and IgE as well as IgG4 and IgE titers of an allergic patient had a significantly stronger positive correlation compared with the control subject (Fisher’s Z transformation, p < 0.05). While the mechanisms of IgGs involvement in allergic responses is still unclear, our finding is in accordance with previous reports suggesting that the levels of IgG4 increased with the increase in IgE in the allergic patients’ sera [26,27].…”
Section: Resultssupporting
confidence: 93%
“…There are four subclasses of IgG (IgG1, IgG2, IgG3 and IgG4). The inhaled allergens were strongly associated with serum IgG4 response [ 33 ]. Production of IgG4 in allergen-specific immunotherapy (AIT) is an immunological hallmark for successful tolerance establishment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%